Study Of The Addition Of Zno (Zinc Oxide) To The Viscosity Value Of Lubricant Products In The Storage Process - Revalina, Fanya Aulia; Neda, Marietta Casta; Akhdan, Gallant Maulana; Khairunnisa, Farida (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to analyze the effect of adding Zinc Oxide (ZnO) to lubricants on the viscosity changes that occur. In the context of engine lubricants, viscosity is a crucial factor in determining the quality and performance of the lubricant. This study uses the Anton Paar svm 3001 Viscometer to measure viscosity at temperatures of 40ºC and 100ºC, as well as the viscosity index using the ASTM test method (ASTM D445 and ASTM D2270). It is hoped that the results of this research will provide a better understanding of the quality of engine lubricants based on the viscosity index, as well as provide guidance in selecting appropriate lubricant additives to meet established lubricant quality standards. Thus, this research can make an important contribution in improving the quality and performance of lubricants available on the market, as well as ensuring the proper distribution of lubricants that meet quality standards.